Evaluasi Determinan Kepuasan Jamaah Travel Umroh: Pendekatan SERVQUAL dan Commitment-Trust Theory - Nurya Ningsih, Ratna; Hasibuan, Abdul Nasser; Cahyani, Utari Evy (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2024)
This study aims to analyze the influence of service quality and trust on the satisfaction of pilgrims using the services of Cahaya Palas Umrah Travel in Padang Lawas Regency. The research adopts a quantitative approach through a survey technique. The population comprises all pilgrims who have used the services of the travel agency, with 198 respondents selected as the sample using the Slovin formula. The data collection instrument was a questionnaire tested for validity and reliability. Data were analyzed using multiple linear regression with SPSS version 25. The findings indicate that both service quality and trust significantly influence pilgrim satisfaction, both partially and simultaneously. These results highlight the importance of improving service quality and fostering trust in maintaining customer loyalty.